Effects of Medium Composition and Carbon Dioxide on Circadian Conidiation in Neurospora - Sargent, Malcolm L. (1972)
Efforts to significantly perturb the timing mechanism, and thus the period, of the rhythm responsible for circadian conidiation in bd, a strain of Neurospora crassa, by altering the medium composition have been unsuccessful. Various salt solutions, sugars, and amino acids do, however, have pronounced effects on growth and conidiation, and thus on the expression and persistence of rhythmicity. Aeration stimulates conidiation in growth-tube cultures, thereby allowing experiments which demonstrate that nearly all strains and species of Neurospora are capable of circadian conidiation. These results extend to Neurospora the generalization that physiological and developmental regulation in all eukaryotic organisms has a circadian component. Aeration also increases the persistence of circadian conidiation suggesting that the damping of rhythmicity previously observed on certain media represents the cessation of conidiation, rather than the stopping of a timing mechanism. Aeration is apparently effective in that it maintains CO(2) levels in growth-tube cultures below a critical concentration. Carbon dioxide was shown to inhibit conidiation in both wildtype and bd strains, with the latter being about 200 times more resistant than the former.